In-silico modelling of the mitogen-activated protein kinase (MAPK) pathway in colorectal cancer: mutations and targeted therapy - Sommariva, Sara; Berra, Silvia; Biddau, Giorgia; Caviglia, Giacomo; Benvenuto, Federico; Piana, Michele (Frontiers in Systems Biology, 2023)
Chemical reaction networks are powerful tools for describing the complex nature of cancer's onset, progression, and therapy. The main reason for their effectiveness is in the fact that these networks can be rather naturally encoded as a dynamical system whose asymptotic solution mimics the proteins' concentration profile at equilibrium. The paper relies on this mathematical approach to investigate global and local effects on the chemical reaction network of the colorectal cancer, triggered by partial and complete mutations occurring in its mitogen-activated protein kinase (MAPK) pathway. Further, this same approach allowed the in-silico modelling and dosage of a multi-target therapeutic intervention that utilizes MAPK as its molecular target.